AN EXAMINATION OF POLICIES REGULATING THE PARTICIPATION OF TRANSGENDER LEARNERS IN SOUTH AFRICAN HIGH SCHOOL SPORTS - Muyenga Mugerwa-Sekawabe (Obiter, 2024)
South African high schools typically adopt a sex-segregated approach to sports teams and, therefore, have “boys” sports teams and “girls” sports teams. This approach is complicated by the increasing number of high school learners who identify openly as transgender. Transgender learners experience the sports policies that South African high schools choose to adopt as falling into one of three broad categories. These categories are: the restrictive approach, the partially inclusive approach and the fully inclusive approach. These approaches vary in terms of what steps they require trans learners to take in order to participate in sports teams that are consistent with their gender identity. School policies must be consistent with the Promotion of Equality and Prevention of Unfair Discrimination Act (PEPUDA) in order to be legally compliant. It is argued that the restrictive approach is inconsistent with PEPUDA, and, therefore, unlawful, as no legitimate purpose underlies it. As legitimate reasons exist for the implementation of partially and fully inclusive policies, it is argued that they are lawful. As both such policies are lawful, policymakers will have a choice regarding which set of policies to adopt. When making this choice, a school must consider which values it seeks to promote. On the one hand, there is the imperative to acknowledge the well-being and dignity of trans learners while, on the other hand, there are legitimate concerns about the fairness of competition. As dignity is both a right that is granted to everyone by the Constitution, and one of its founding values, it is argued that fully inclusive policies should be favoured as they result in the validation of trans learners’ dignity. Furthermore, it is argued that high school sports should serve broader educational goals, such as teaching high school learners that their trans peers deserve the chance to live their truth in full.